Conscious business in Germany : assessing the current situation and creating an outlook for a new paradigm /: assessing the current situation and creating an outlook for a new paradigm. ([2018]) - Stahlhofer, Nicolas Josef; Schmidkonz, Christian, 1972-; Kraft, Patricia
No abstract available